2015
DOI: 10.1111/trf.13098
|View full text |Cite
|
Sign up to set email alerts
|

Making thawed universal donor plasma available rapidly for massively bleeding trauma patients: experience from the Pragmatic, Randomized Optimal Platelets and Plasma Ratios (PROPPR) trial

Abstract: Background The Pragmatic Randomized Optimal Platelets and Plasma Ratios (PROPPR) trial was a randomized clinical trial comparing survival after transfusion of 2 different blood component ratios for emergency resuscitation of traumatic massive hemorrhage. Transfusion services supporting the study were expected to provide thawed plasma, platelets and red blood cells within 10 minutes of request. Study Design and Methods At the 12 Level 1 trauma centers participating in PROPPR, blood components transfused and d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
59
0
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
5

Relationship

3
7

Authors

Journals

citations
Cited by 74 publications
(63 citation statements)
references
References 19 publications
1
59
0
3
Order By: Relevance
“…Prior to starting the study, and as part of site training and verification, each site was evaluated for the ability of its blood bank to randomize, prepare, and deliver the first MTP cooler to the bedside within ten minutes, as well as to prepare and deliver subsequent coolers on-demand. 11 As such, time of arrival, time to MTP activation and time to arrival of initial and each subsequent cooler were collected as time points of interest. The content of each MTP cooler was identical between centers, varying only by randomization group ( i.e.…”
Section: Methodsmentioning
confidence: 99%
“…Prior to starting the study, and as part of site training and verification, each site was evaluated for the ability of its blood bank to randomize, prepare, and deliver the first MTP cooler to the bedside within ten minutes, as well as to prepare and deliver subsequent coolers on-demand. 11 As such, time of arrival, time to MTP activation and time to arrival of initial and each subsequent cooler were collected as time points of interest. The content of each MTP cooler was identical between centers, varying only by randomization group ( i.e.…”
Section: Methodsmentioning
confidence: 99%
“…A number of studies have reported that in patients receiving higher ratios there is an increase in the amount of plasma transfused and an increased incidence of transfusion-related adverse events without a survival benefit, however, these concerns were not confirmed in the PROPPR trial (49) (50) (51). Time to delivery of product replacement in PROPPR was rapidly achieved without significant wastage but this is dependent on having thawed product available 24 hours a day in either the trauma unit or blood bank (52). The impressive delivery of blood component therapy as described in the PROPPR trial may be difficult to translate into routine clinical practise (53).…”
Section: Major Haemorrhage Protocols (Mhp)mentioning
confidence: 99%
“…The transition of large trauma centers to thawed plasma has led to a near 50% decrease in time to plasma transfusion 23,24 resulting in an independent predictor of decreased mortality. 23 The trade-off with the increasing use of thawed plasma is the 2.2% wastage rate, most of which is limited AB donor plasma.…”
Section: Discussionmentioning
confidence: 99%